2006
DOI: 10.1902/jop.2006.060101
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Sealing Ability of Two Materials at Five Different Implant‐Abutment Surfaces

Abstract: 1) Materials tested were not able to prevent contamination over 63 days. 2) Bacterial contamination was verified after 14 and 35 days in the control and experimental groups, respectively. 3) Although materials tested had demonstrated similar sealing capacities, dental implants showed bacterial contamination regardless of their external or internal hexagonal configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
23

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 12 publications
(14 reference statements)
1
47
1
23
Order By: Relevance
“…Morse taper implant systems provided a better seal compared with external hexagonal systems with respect to the amount and time of bacterial leakage, Duarte et al 29 found that bacteria penetrated the internal aspect of implants from the outside media regardless of the internal or external hexagonal connection. The results of the present investigation agree with those reported by Jansen et al, 30 in which the three conical abutment interfaces evaluated showed evidence of leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Morse taper implant systems provided a better seal compared with external hexagonal systems with respect to the amount and time of bacterial leakage, Duarte et al 29 found that bacteria penetrated the internal aspect of implants from the outside media regardless of the internal or external hexagonal connection. The results of the present investigation agree with those reported by Jansen et al, 30 in which the three conical abutment interfaces evaluated showed evidence of leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [8][9][10][11] have demonstrated that platform-switched abutments may not only reduce the early peri-implant bone loss and increase the biomechanical support available to the implant, but also may improve esthetics. Baumgarten and coworkers [6] suggested that the platform switching technique is useful when shorter implants are used, when implants are placed in esthetic zone, and when a larger implant is desirable but prosthetic space is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This connection shifts the perimeter of the implant-abutment junction inward towards the central axis (the middle of the implant), potentially improving the distribution of forces and placing the implant-abutment gap away from the peri-implant bone [4,5]. It has been suggested that the inward shift of the implant-abutment gap may physically minimize the impact of the inflammatory cell infiltrate in the peri implant tissues, potentially reducing bone loss [2,[6][7][8][9][10][11]. From a biomechanical perspective, previous in vitro studies [12][13][14][15][16][17] have shown reduced levels of stress on peri-implant bone in platform-switched implants relative to matched implant-abutment diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and in vitro evaluations indicate that connections between components are more stable in the internal hexagonal system, in which the larger contact area between internal implant and abutments walls favors force distribution and preserves the abutment screw (Norton et al, 1997;Mollersten et al, 1997;Binon et al, 2000;Finger et al, 2003). Microbiological studies, however, do not show significant differences between hexagonal internal or external connections, when bacterial leakage is concerned (Jansen et al, 1997;Steinebrunner et al, 2005;Duarte et al, 2006). The Morse cone connection system has recently been introduced and is becoming increasingly popular in implant dentistry.…”
Section: Design Features and Marginal Fit Of Implant Componentsmentioning
confidence: 99%